2016
DOI: 10.1038/srep37145
|View full text |Cite
|
Sign up to set email alerts
|

Use of Zebrafish Larvae as a Multi-Endpoint Platform to Characterize the Toxicity Profile of Silica Nanoparticles

Abstract: Nanomaterials are being extensively produced and applied in society. Human and environmental exposures are, therefore, inevitable and so increased attention is being given to nanotoxicity. While silica nanoparticles (NP) are one of the top five nanomaterials found in consumer and biomedical products, their toxicity profile is poorly characterized. In this study, we investigated the toxicity of silica nanoparticles with diameters 20, 50 and 80 nm using an in vivo zebrafish platform that analyzes multiple endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 53 publications
1
34
0
Order By: Relevance
“…No significant developmental defects and malformations are seen in either concentration of SNPs. These results are correlated with the studies of chemically synthesized SNPs and fluorescent SNPs used for embryonic toxicity which shows significant embryonic toxicity [28,29]. However, in our study, bamboo leaf derived amorphous silica particles exhibits better biocompatibility and nontoxic effect in terms of zebrafish embryonic toxic assays in the early developmental stages.…”
Section: Embryonic Toxicitysupporting
confidence: 86%
“…No significant developmental defects and malformations are seen in either concentration of SNPs. These results are correlated with the studies of chemically synthesized SNPs and fluorescent SNPs used for embryonic toxicity which shows significant embryonic toxicity [28,29]. However, in our study, bamboo leaf derived amorphous silica particles exhibits better biocompatibility and nontoxic effect in terms of zebrafish embryonic toxic assays in the early developmental stages.…”
Section: Embryonic Toxicitysupporting
confidence: 86%
“…In terms of manufacture processes, SiO 2 NPs are among the top five nanomaterials in commercial products. These nanomaterials, namely in a powdered form, have found relevant properties that make SiO 2 NPs useful in chemical, biotechnological and plastic manufacturing industries, electronics, biomedicine and agriculture [2][3][4]. However, the large-scale production of SiO 2 NPs have raised also concerns about their potential adverse effects, namely due to accumulation in specific environments [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the effects of SiO 2 NPs in different soil and aquatic organisms [4,[10][11][12], however, the knowledge about the impact of SiO 2 NPs exposure is still limited, namely on soil organisms. Moreover, contradictory results have been reported regarding the effects of SiO 2 NPs on survival; some studies reported no effects on Enchytraeus crypticus, Caenorhabditis elegans, Daphnia magna and Danio rerio [4,11,12], while others reported decreased survival on D. magna and D. rerio [13,14]. Regarding the effects of SiO 2 NPs on the behavior of the organisms, the few studies available mostly agree that these nanomaterials have adverse effects in this endpoint, by altering the locomotion pattern and reducing the speed of movements of C. elegans [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish are oviparous organisms with external fertilization, transparent eggs, and temporospatial development pattern. [3][4][5][6] Studies have revealed that zebrafish can spontaneously develop a variety of tumors, which can be induced either by chemical mutagen exposure or with transgenic techniques. 7 Several models have been generated successfully, including models of leukemia, melanoma, and rhabdomyosarcoma.…”
Section: Introductionmentioning
confidence: 99%